2019
DOI: 10.1016/j.jaci.2019.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial demonstrating the benefits of delta inulin adjuvanted immunotherapy in patients with bee venom allergy

Abstract: Background: Allergic reactions to Hymenoptera insect stings remain a major global clinical problem. Although effective, parenteral desensitization regimens require use of costly venom extracts and require frequent visits over extended periods of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 53 publications
(56 reference statements)
0
19
0
1
Order By: Relevance
“…The protective effect of the vaccine was associated with the targeted expansion of lung-resident T RM and was dependent on IL-17 recruitment of phagocytic cells to the lung and enhanced priming of T cells in the mLN. Advax-containing vaccines have proven safe and immunogenic in human trials against viral infection and allergy 19 , 46 , 47 and are safe and effective in pre-clinical trials as inhaled formulations 21 . Thus CysVac2/Advax warrants further study to assess its suitability as a pulmonary vaccine for the control of TB in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of the vaccine was associated with the targeted expansion of lung-resident T RM and was dependent on IL-17 recruitment of phagocytic cells to the lung and enhanced priming of T cells in the mLN. Advax-containing vaccines have proven safe and immunogenic in human trials against viral infection and allergy 19 , 46 , 47 and are safe and effective in pre-clinical trials as inhaled formulations 21 . Thus CysVac2/Advax warrants further study to assess its suitability as a pulmonary vaccine for the control of TB in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In published studies covering many years of research, delta inulin has been shown to provide a robust humoral and cellular immune response when formulated with recombinant vaccine antigens. Advax adjuvant has recently also successfully been tested in several human trials including vaccine studies to prevent seasonal and pandemic influenza, hepatitis B, and hyperallergic reactions to insect venom [ 123 ]. Compared to the controls, the Advax adjuvant [ 56 , 123 ] seems to improve antibody and T-cell responses, while being safe and well-tolerated [ 54 ].…”
Section: Adjuvantsmentioning
confidence: 99%
“…Advax adjuvant has recently also successfully been tested in several human trials including vaccine studies to prevent seasonal and pandemic influenza, hepatitis B, and hyperallergic reactions to insect venom [ 123 ]. Compared to the controls, the Advax adjuvant [ 56 , 123 ] seems to improve antibody and T-cell responses, while being safe and well-tolerated [ 54 ]. It should however be noted that Advax is still a relatively new adjuvant, which has only been tested on small groups of patients and has not yet been part of a marketed vaccine.…”
Section: Adjuvantsmentioning
confidence: 99%
“…In published studies covering many years of research, delta inulin has been shown to provide a robust humoral and cellular immune response when formulated with recombinant vaccine antigens. Advax adjuvant has recently also successfully been tested in several human trials including vaccine studies to prevent seasonal and pandemic influenza, hepatitis B, and hyperallergic reactions to insect venom [130]. Compared to the controls, the Advax adjuvant [52,130] seems to improve antibody and T-cell responses, while being safe and well-tolerated [50].…”
Section: Advaxmentioning
confidence: 99%